Effect of α-tocopherol in alleviating the lipopolysaccharide-induced acute lung injury via inhibiting nuclear factor kappa-B signaling pathways. Issue 2 (1st February 2022) - Hu, Mu; Yang, Jielai; Xu, Yang
ABSTRACT: Acute respiratory distress syndrome (ARDS) leads to the acute lung injury (ALI), a form of diffused alveolars injury, accompanied by severe inflammation and oxidative damage of alveolar epithelial cells. α-Tocopherol (α-TOH), one of the eight isoforms of vitamin E, is a natural antioxidant-free radical. We aimed to understand the effect of α-TOH and mechanism involved in inducing the ALI. Lipopolysaccharide (LPS) is injected into the trachea of mice to generate ALI mouse models. α-TOH was used to administrate the mice intragastrically to detect the expression of inflammatory factors and antioxidant molecules by enzyme linked immunosorbent assay, hematoxylin–eosin staining and immunohistochemical staining. Mouse alveolar epithelial cell line (MLE-12 cells) was used to determine the effect of α-TOH on alveolar epithelial cells. Inflammatory factors such as, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α shows significant increase in the lung tissues of the mice induced by LPS and reduction in the expressions of superoxide dismutase (SOD)1/2 and glutathione peroxidase (GSH-Px). After treatment with α-TOH, the inflammation and oxidative stress levels shows substantial reduction in the lung tissues of the mice. Moreover, α-TOH also increases the proliferation ability of MLE-12 cells in vitro and reduces apoptosis level. In addition, α-TOH reduces p65 phosphorylation and nuclear translocation in alveolar epithelial cells in vivo and in vitro, thus, inhibiting the activity of the nuclear factor kappa-B (NF-κB) signaling pathway. α-TOH reduces the inflammation and oxidative stress of lung tissue by inhibiting the NF-κB signaling pathway, thereby alleviating the LPS-induced ALI. Graphical abstract: uf0001